2017
DOI: 10.1002/pc.24650
|View full text |Cite
|
Sign up to set email alerts
|

Competition effect of shear‐induced nuclei and multiwalled carbon nanotubes (MWCNT) on β‐isotactic polypropylene (iPP) formation in preshear injection‐molded iPP/MWCNT nanocomposites

Abstract: In this study, the influence of multiwalled carbon nanotubes (MWCNT) on β‐isotactic polypropylene (iPP) formation in preshear injection‐molded iPP/MWCNT nanocomposites is investigated layer by layer by wide angle X‐ray diffraction (WAXD). WAXD results suggest that in preshear injection‐molded pure iPP, β‐iPP exists in not only the shear region, but also the core region as a result of preshear‐induced nucleation. The addition of MWCNT can inhibit the β‐iPP formation. As the depth away from the specimen surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In previous studies, the heterogeneous nucleation ability of MWCNTs has been confirmed by some literature. 50,51 These scattered MWCNTs agglomerates, on the one hand, further increase the nucleation sites of PA66. On the other hand, they also hinder the growth of PA66 grains, making the grain size of PA66/MWCNTs-GF composites significantly smaller than that of pure PA66.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the heterogeneous nucleation ability of MWCNTs has been confirmed by some literature. 50,51 These scattered MWCNTs agglomerates, on the one hand, further increase the nucleation sites of PA66. On the other hand, they also hinder the growth of PA66 grains, making the grain size of PA66/MWCNTs-GF composites significantly smaller than that of pure PA66.…”
Section: Resultsmentioning
confidence: 99%
“…Melt extrusion molding is one of the most important polymer melt processing techniques by which common thermoplastic polymers can be processed into macrosized but microstructure controllable products. More importantly, it shows facile, solvent-free, low-cost, high-efficiency, and large-scale features. In practice, targeted for specific practical applications, two immiscible polymers are usually melt blended by extruder, resulting in an immiscible heterogeneous biphase system.…”
Section: Introductionmentioning
confidence: 99%
“…Among a variety of polymers filled with CNTs, isotactic polypropylene (iPP) is one of the most preferred thermoplastics that is commonly reinforced with CNTs [8,9,10]. It has been reported that mechanical properties of iPP such as tensile strength, modulus, and fracture toughness can increase dramatically at very low CNTs contents (<1%) [4,11], owing to the large nanocarbon/polymer interface arising from their high surface-to-volume ratio.…”
Section: Introductionmentioning
confidence: 99%